A Constitutive Model for Saturated Gravelly Sand Based on Higher-Order Dilatancy Equation. (10th July 2020) - Zhang, Dongjie; Luo, Fei; Zhu, Zhanyuan; Luo, Bin; Li, Jing; Xu, Zihan; Liu, Jiaming
Abstract : A standard stress path triaxial test system was applied to carry out conventional triaxial shearing tests for gravelly sands under confining pressures ranging from 50 kPa to 400 kPa at the initial relative densities of 0.15, 0.35, 0.55, and 0.75, respectively. The test results show that all the samples of gravelly sand present strain hardening and shear contraction during the process of shearing test. Additionally, gravelly sands are significantly affected by the initial relative density. The hardening degree of gravelly sand samples rises in line with increasing initial relative densities during shearing tests. When initial relative densities D r are at 0.15 and 0.35, the volume shrinkage of samples decreases with the increasing confining pressures. Instead, when initial relative densities D r are at 0.55 and 0.75, the volume shrinkage of samples increases with the growth of confining pressures. To describe these triaxial shearing mechanical properties of gravelly sands, a higher-order dilatancy equation was proposed based on the concept of a super yield surface. A constitutive model which can describe the mechanical properties of gravelly sand was established when the associated flow laws were applied to compare with the results of the triaxial shearing test under the consolidated drained condition. The comparison results showed that the proposed model can reflect the strain hardening and shear contraction characteristics of gravelly sands from low to high confining pressures under different initial relative densities.